2018
DOI: 10.1002/admi.201800303
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Like Nitrogen‐Doped Carbon Nanosheet Prepared from Direct Calcination of Dopamine Confined by g‐C3N4 for Oxygen Reduction

Abstract: Abstract2D carbon nanosheet provides an attractive prospect in the field of electrochemical catalysis, and how to prepare atomic level 2D carbon nanosheet with good electrochemical performance by an easy and efficient method is still a big challenge. Herein, graphene‐like N‐doped carbon nanosheet with the thickness of 0.6–2 nm is prepared by one‐step and solvent‐free method of pyrolyzing dopamine (DA) confined by graphitic carbon nitride (g‐C3N4). Pyrocondensation polymerization of DA within the interlayers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…2 b). The intensity ratio of D to G band ( I D / I G ) manifests the degree of graphitization of carbon materials [ 44 ]. Among the as-synthesized catalysts, the I D / I G (1.25) of Fe–N–C/FeN is higher than those of Fe–N–C (0.86), Fe–N–C/control (1.05) and Fe–N–C/N (1.06).…”
Section: Resultsmentioning
confidence: 99%
“…2 b). The intensity ratio of D to G band ( I D / I G ) manifests the degree of graphitization of carbon materials [ 44 ]. Among the as-synthesized catalysts, the I D / I G (1.25) of Fe–N–C/FeN is higher than those of Fe–N–C (0.86), Fe–N–C/control (1.05) and Fe–N–C/N (1.06).…”
Section: Resultsmentioning
confidence: 99%
“…The change in relative intensity suggested that the N 2 -cooled g-C 3 N 4 has crystal distraction in its structure. 57…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen-carbon (NÀ C) materials were also reported and used as ORR catalysts. [55][56][57][58][59][60][61][62][63] Herein, we focus on the MÀ NÀ C based electrocatalysts. From the point view of morphology, these MÀ NÀ C electrocatalysts are composed of one-dimensional (1D), twodimensional (2D), three-dimensional (3D) and multi-dimensional (MD) materials.…”
Section: The Oxygen Reduction Reaction and Its Electrochemical Evaluamentioning
confidence: 99%
“…Figure c shows a typical molecular structure of a M−N−C catalyst with metal atom coordinated on N‐doped carbon material. The nitrogen‐carbon (N−C) materials were also reported and used as ORR catalysts . Herein, we focus on the M−N−C based electrocatalysts.…”
Section: The Oxygen Reduction Reaction and Its Electrochemical Evaluamentioning
confidence: 99%